Alternative Crops and Cropping Systems - Konvalina, Petr (IntechOpen, 2016)
Alternative crops and cropping systems have importance in whole agricultural sector. As the name suggests, it is an alternative that can currently represent only a small economic importance. On the other hand, in some areas pose a new progressive direction, which has the potential to expand in the future. The goal was to write a book where as many different existing studies as possible could be presented in a single volume, making it easy for the reader to compare methods, results and conclusions. As a result, studies from countries such as South Africa, Zimbabwe, Poland, The Czech Republic, Mexico and Japan have been compiled into one book. I believe that the opportunity to compare results and conclusions from different countries and continents will create a new perspective in alternative crops and cropping systems. I hope that our book will help researchers and students all over the world to attain new and interesting results in the field of alternative crops and cropping systems.